Vertical and horizontal distribution of ascending Atlantic salmon in power plant tailrace channels - Sutela, Tapio; Orell, Panu; Huusko, Ari; Jaukkuri, Mikko; Huusko, Riina; Mäki-Petäys, Aki; Erkinaro, Jaakko (Fisheries Management and Ecology)
2018